Morphogenesis of hepatitis A virus: isolation and characterization of subviral particles. - Anderson, D A (1990)
The morphogenesis of hepatitis A virus (HAV) in BS-C-1 cells was examined by immunoblotting with antisera to capsid proteins and labeling of virus-specific proteins with L-[35S]methionine. Antiserum to VP2 detected two virus-specific proteins with apparent molecular masses of 30.6 and 30 kDa, representing VP0 and VP2, while antiserum to VP1 detected proteins with molecular masses of 33 and 40 kDa, representing VP1 and a virus-specific protein which we designated PX, respectively. Sedimentation of cell lysates revealed the presence of virions, procapsids, and pentamers, but particles analogous to the protomers of other picornaviruses were not detected. Although provirions and virions were not found as discrete species in our gradient system, it was evident that the rate of sedimentation was proportional to the relative amounts of VP0 and VP2 in particles, with slower-sedimenting particles (provirions) containing predominantly VP0 rather than VP2. Procapsids contained VP0 in addition to VP1 and VP3. Pentamers also contained VP0, but PX was present rather than VP1. These results suggest that PX is a precursor to VP1 and is most likely 1D2A. Primary cleavage of the viral polyprotein also occurs at the 2A-2B junction in cardioviruses and aphthoviruses, but assembly of pentamers containing 1D2A has not been reported for those viruses. The absence of detectable levels of protomers suggests a high efficiency of pentamer formation, which may be related to the high efficiency of viral RNA encapsidation for HAV (D.A. Anderson, B.C. Ross, and S.A. Locarnini, J. Virol. 62:4201-4206, 1988). The results of this study reveal further unusual aspects of the HAV replicative cycle which distinguish it from other picornaviruses and may contribute to its restricted replication in cell culture.